Comparative study on fabrication of coated mesh for oil/water separation / Affandy Rahim and Faraziehan Senusi - Rahim, Affandy (2020)
Oil pollution has become a major global issue that can cause harm to the environment. There are many conventional methods such as oil skimming, dispersant, in situ burning, however, these methods proposed certain drawbacks such as secondary pollution, expensive equipment, and timeconsuming. In response to this problem, super-wetting material is introduced as an alternative. Pristine stainless steel mesh has an amphiphilic characteristic whereby it unable to separate oil/water mixture effectively. The objectives for this study are to determine the effect of different fabrication methods, towards the modification stainless-steel mesh and to evaluate the surface characteristics of superhydrophobic and superoleophilic stainless steel mesh using different characterization methods. In the review process, the main library databases cover most of the papers are Science Direct, Scopus, and Google Scholar. The types of method that have been reviewed in this comparative study are dip/immersion and spray coating method. The characterization involves in this study are surface morphology, surface composition analyses, and surface wettability. In addition, oil/water separation efficiency was conducted by using gravitydriven filtration. In the surface composition analysis, different absorption peaks can be observed due to the different functional groups introduced on coating material. In the surface wettability analysis, it is found that the coated meshes exhibit high water contact angle and low oil contact angle. Other than that, these coated meshes also have high oil/water separation efficiency as superhydrophobic and superoleophilic characteristics are employed.